2014
DOI: 10.3892/or.2014.3219
|View full text |Cite
|
Sign up to set email alerts
|

HGF and the regulation of tight junctions in human prostate cancer cells

Abstract: Hepatocyte growth factor (HGF) may impact the metastasis of prostate cancer via its action on prostate stem cells or their progeny. Tight junctions (TJs) are crucial to the process of metastasis and have been previously shown to be regulated by HGF. The present study aimed to evaluate the effect of HGF on the function of TJs in human prostate epithelial, prostate stem cell-like and prostate cancer cell lines. Four human prostate cancer cell lines (PC-3, DU-145, PZHPV-7, CaHPV-10), normal adult prostate parenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Tight junctions are responsible for the regulation of endothelial permeability 22,23 Endothelial tight junctions are necessary to prevent cancer cells freely migrating into the circulation during metastasis 24,25 Cancer blood vessels are more permeable structures than those in normal tissue vessels, and they assist cancer metastasis 24,26 The decrease or loss of claudins 1, 5, occludin and ZO-1 in many cancers has been reported 24,27,28 As described above, CLIC2 may be involved in the formation and/or maintenance of tight junctions in normal blood vessel endothelia, which may lead to the inhibition of the hematogenous metastasis of cancer cells. Indeed, this study demonstrated that the knockdown of CLIC2 in HUVECs increased the FBS-induced transmigration of human cancer cells through a HUVEC monolayer.…”
Section: Predominant Expression Of Clic2 In Non-cancer Tissues and Itmentioning
confidence: 99%
See 1 more Smart Citation
“…Tight junctions are responsible for the regulation of endothelial permeability 22,23 Endothelial tight junctions are necessary to prevent cancer cells freely migrating into the circulation during metastasis 24,25 Cancer blood vessels are more permeable structures than those in normal tissue vessels, and they assist cancer metastasis 24,26 The decrease or loss of claudins 1, 5, occludin and ZO-1 in many cancers has been reported 24,27,28 As described above, CLIC2 may be involved in the formation and/or maintenance of tight junctions in normal blood vessel endothelia, which may lead to the inhibition of the hematogenous metastasis of cancer cells. Indeed, this study demonstrated that the knockdown of CLIC2 in HUVECs increased the FBS-induced transmigration of human cancer cells through a HUVEC monolayer.…”
Section: Predominant Expression Of Clic2 In Non-cancer Tissues and Itmentioning
confidence: 99%
“…Which factors cause the loss of CLIC2 or tight junction proteins in tumor endothelial cells (TECs)? Cancer cell-derived humoral factor(s) may enhance the blood vessel permeability 29 Among these humoral factors, hepatocyte growth factor (HGF) may increase the permeability of blood vessels in liver cancers 24,25 HGF was shown to suppress the expression of tight junction proteins including ZO-1, claudin 1 and occludin. Serum HGF levels are increased in various liver diseases such as acute and chronic hepatitis, liver cirrhosis and HCC, and AST values were positively correlated to the serum HGF level 30 The present findings showed that CLIC2 expression was reduced in non-cancer liver tissues with higher AST values or fibrosis.…”
Section: Potential Involvement Of Hgf and Vegf In The Decreased Exprementioning
confidence: 99%
“…TJP3 is required for 4-(furan-2-yl)-2-(pyridin-2-yl)-5, 6-dihydro-1, 10-phenanthroline (FPDHP)-regulated cancer therapy (32). In prostate cancer, hepatocyte growth factor (HGF) modulates metastasis through TJ proteins including TJP3 (33). TJP3 is proposed as a diagnostic tool for lung cancer (34) and is associated with poor prognosis in patients with breast cancer (35).…”
Section: Introductionmentioning
confidence: 99%
“…These results, therefore, suggest that change to cell invasion in prostate cancer cells is independent of HGF signalling. Previous studies had demonstrated a decreased TER and decreased TJ protein expression and membrane localisation and, therefore, a decreased junctional integrity with the HGF treatment [ 44 , 45 ]. There was no effect with the HGF treatment when HAVcR-1 was overexpressed or knocked-down in PC-3 cells or when overexpressed in PZ-HPV-7 cells.…”
Section: Discussionmentioning
confidence: 99%